Turning losses into gains : SIDS and multilateral trade liberalisation in agriculture (UN New YorkUS, 2003)
Examines the pattern of agricultural trade of SIDS in the world market. Assesses the impact of continued multilateral agricultural liberalization on SIDS using UNCTAD's Agricultural Trade Policy Simulation Model (ATPSM). Provides an empirical examination of the impact of 'small-islandness' on the agricultural trading environment of SIDS. Identifies what types of rules, or 'modalities' are desirable from their own trade and development perspective in the continuing process of multilateral agricultural liberalization. Presents four cases studies covering the Indian Ocean islands, the Pacific islands, the Windward Islands and Barbados.
Keywords: TRADE LIBERALIZATION